Recent advances in brazing fillers for joining of dissimilar materials - Ahn, Byungmin (Metals, 2021)
Brazing fillers for joining applications are essential for manufacturing and designing advanced materials. Several types of brazing fillers have been developed in recent decades to join similar or different engineering materials. Important parts of automotive and aircraft components, including steel, are often joined by brazing. In addition, ceramic components in microwave devices and circuits have been joined with a high level of integration in microelectronic devices. Similarly, in the medical field, metallic implants have been brazed to ceramic dental crowns. These advances have made human life more convenient. However, in brazing, there are certain issues with intermetallic compound (IMC) formation and residual stresses in joints at high temperatures. Nanoparticle-reinforced fillers have been proposed to control IMCs, but there are other dispersion and particle segregation issues at the joints. In this study, various types of brazing fillers, joint fabrication processes, and brazing technologies developed in recent decades are reviewed. Furthermore, new developments in brazing materials and their specific applications are presented. Finally, the emerging areas in brazing, including the recent entropy-modified brazing fillers for various structural and technological fields, are discussed.
Keywords: Automotive; Brazing; Dissimilar; Joining; Joint; Laser; Melting